Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/014556131309200211
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Surgery Alone for Human-Papillomavirus–Associated Oropharyngeal Squamous Cell Carcinoma

Abstract: The aim of this retrospective study was to describe the oncologic and functional results of treating oropharyngeal squamous cell carcinoma with transoral robotic surgery and neck dissection as monotherapy. A review was performed, including all patients who underwent transoral robotic surgery and neck dissection as the only means of therapy for oropharyngeal carcinoma from March 2007 to July 2009 at a single tertiary care academic medical center. We reviewed all cases with ≥ 24-month follow-up. Functional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 16 publications
5
60
0
Order By: Relevance
“…Despite most patients doing well, up to 25% of patients relapse in their disease in the first 3 years, most frequently as a LRR. 4,5,8,9,22 DM occur slightly less frequently in 2%-12%. 4,5,22,23 Our rates of LRR and DM after TOS AE adjuvant therapy compare well to these studies with 7.4% and 6.3%, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite most patients doing well, up to 25% of patients relapse in their disease in the first 3 years, most frequently as a LRR. 4,5,8,9,22 DM occur slightly less frequently in 2%-12%. 4,5,22,23 Our rates of LRR and DM after TOS AE adjuvant therapy compare well to these studies with 7.4% and 6.3%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 It is also more responsive to treatment and some series report survival rates above 90%. [6][7][8][9] Given the high degree of treatment-related morbidity after standard management for oropharyngeal cancer, multiple studies are currently underway to investigate deescalation of therapy in pursuit of decreasing long-and short-term treatment-related sequelae while still maintaining the same rate of disease control. 10 Although, most patients have a favorable prognosis, a subset of patients relapses in their disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well-established that HPV positivity is a favorable prognostic indicator for patients with oropharyngeal cancer, 12 and prior studies have shown this to be true for patients treated with transoral techniques as well. 7,26 Our study is the first single TORS cohort to demonstrate a statistically significant difference in survival between HPV-positive and HPV-negative patients. These findings suggest that HPV status may be helpful in designing a tailored therapy for patients.…”
Section: Discussionmentioning
confidence: 87%
“…In our cohort, HPV status was even more important than nodal staging, which is consistent with previous findings. 26 This single-institution study is limited by small sample size and limited length of follow-up. Multi-institutional TORS studies are underway and will add more robust data to the TORS literature.…”
Section: Discussionmentioning
confidence: 99%